Reformulation of the Law on Pharmacy Practices on Drug Dispensing by Independent Doctors' Practices, Reviewed from Their Purposes, Effectiveness and Legal Harmonization - Adib Gunawan; Nandang Sambas; Sri Ratna Suminar (Global Writing Academica Researching and Publishing, 2026)
The purpose of this study is to analyze pharmaceutical practice regulations on drug dispensing by independent practicing physicians and reformulate pharmaceutical practice regulations on drug dispensing by independent practicing physicians in terms of legal benefits. This study uses a normative juridical method with a statutory approach. Data were obtained through literature and empirical studies, analyzed qualitatively descriptively. The results showed that 390 doctors in Bandung City performed drug dispensing. Research in Denpasar City and Bandar Lampung also showed a relatively high rate of drug dispensing by independent practicing physicians. The reason for doctors dispensing is to make it easier for patients, the local government through DPMPTSP which is mandated by law to issue practice permits for health workers, does not allow pharmacists to create SIPs in independent medical practices, but on the other hand, as per Law No. 17 of 2023, BPJS Regulation No. Law No. 1 of 2014 also categorizes independent physician practices as health facilities, where capitation funds include medication costs. The physician discovered/alleged that a non-pharmacist pharmacy was providing non-prescription medications that should have been prescribed. Pharmacists should be permitted to create a SIP for independent physician practices. Regional regulations (through the DPMPTSP) that prohibit pharmacists from creating SIPs for independent physician practices should be reformulated to allow them.